Retinal Neural Layer Thickness and Contrast Sensitivity in Type 2 Diabetes Without Clinical Retinopathy: A Cross-Sectional Study - Ramzi Amin; Ririn Rahayu; Petty Purwanita; Muhammad Aulia Molid Ogest Putra Calisanie (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Retinal neural dysfunction may occur in type 2 diabetes mellitus (T2DM) before clinically visible diabetic retinopathy. Objective: We evaluated whether retinal nerve fiber layer (RNFL) and ganglion cell-inner plexiform layer (GCL-IPL) thickness were associated with contrast sensitivity in adults with T2DM without clinical retinopathy. Methods: This cross-sectional study included 30 eyes from 16 participants examined from September 2024 to June 2025. Swept-source optical coherence tomography measured average and quadrant RNFL thickness and macular GCL-IPL thickness. Monocular contrast sensitivity was assessed with the Pelli-Robson chart. Source-reported analyses included exploratory Spearman correlations, generalized estimating equations (GEE) for inter-eye clustering, and exploratory receiver operating characteristic (ROC) analysis. Results: Mean RNFL thickness was 101.3 ± 12.55 µm, GCL-IPL thickness was 81.53 ± 7.34 µm, and contrast sensitivity was 1.773 ± 0.227 logCS. Eye-level correlations with contrast sensitivity were ρ=0.758 for GCL-IPL and ρ=0.640 for average RNFL (both source-reported p<0.001). In the exploratory GEE model, coefficients were 0.0104 logCS per µm for GCL-IPL (95% CI 0.001-0.019) and 0.0062 for RNFL (95% CI 0.001-0.011). Exploratory AUCs were 0.872 and 0.804, respectively. Conclusion: Thicker GCL-IPL and RNFL measurements were associated with better contrast sensitivity in this small cohort. The estimates are hypothesis-generating and require confirmation with participant-level data, larger samples, and external validation before clinical use.